Explaining firms export behaviour: the role of RD and spillovers - Salvador Barrios Cobos; Holger Görg; Eric Strobl (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2001)
We examine the importance of a firm's own R&D activity and intra-sectoral spillovers on the decision to export and the export intensity using firm level panel data for Spain for the period 1990 to 1998. Our results are in line with preceding findings on the role played by firmspecific variables such as age, firm size, productivity and workers' skills. In addition, we show that export and R&D spillovers, either from MNEs or domestic firms in the sector, have a different impact on Spanish and foreign firms, the latter generally benefiting from positive spillovers. Further evidence shows a larger marginal impact of R&D spillovers on export intensity of Spanish firms exporting to other OECD countries than those exporting to non- OECD nations.
Keywords: 330; Exportindustrie; Multinationales Unternehmen; Industrielle Forschung; Spillover-Effekt; Spanien